2007
DOI: 10.1097/01.rct.0000238005.42129.64
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Endometrial Cancer and Clear Cell Cancer

Abstract: The magnetic resonance imaging appearance of the internal slit in solid components and the presence of endometrial disease are key factors in differentiating endometrioid cancer from clear cell cancer, although lesion locularity and growth pattern are not specific in both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 4 publications
0
5
2
2
Order By: Relevance
“…In our study, however, only CCC showed a significantly higher incidence of endometriosis when compared with SC in the univariate analysis. In addition, CCC was reported to appear as a larger unilocular cystic mass with eccentric mural nodules [ 27 , 28 ], whereas in our study a large number of CCC had multilocular cystic masses. Therefore, differentiating CCC from EC based only on the imaging findings seems to be difficult.…”
Section: Resultscontrasting
confidence: 56%
“…In our study, however, only CCC showed a significantly higher incidence of endometriosis when compared with SC in the univariate analysis. In addition, CCC was reported to appear as a larger unilocular cystic mass with eccentric mural nodules [ 27 , 28 ], whereas in our study a large number of CCC had multilocular cystic masses. Therefore, differentiating CCC from EC based only on the imaging findings seems to be difficult.…”
Section: Resultscontrasting
confidence: 56%
“…The following MRI morphologic features were assessed with both T1 and T2 phases, such as the maximal diameter of the cyst, tumor margin, multilocularity, growth patterns and surface irregularities of mural nodules, characteristics of solid components, and the presence of malignant ascites; all of these features are considered significant factors in distinguishing between benign and malignant ovarian tumors [23, 24]. A mural nodule was defined as a wall-based lesion projecting into the cystic space.…”
Section: Methodsmentioning
confidence: 99%
“…However, MRI findings, such as tumor size, fluid signal intensity, post-contrast enhancement pattern, and mean apparent diffusion coefficient values of the solid portion, may not be useful parameters for differentiating CCC from EC [22]. Manabe et al reported that the presence of endometrial disease was a key factor in differentiating EC from CCC [23]. Another MRI morphological feature of EC comprised an internal slit in the solid components [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Manabe T, et al [11] reported that endometrioid cancer had a predominantly multilocular appearance, and clear cell carcinoma had almost equally multilocular and unilocular appearances. In the present study, benign lesions (groups 1 and 3) tended to show a unilocular appearance and be small-sized.…”
Section: Size Thickness Of the Wall The Septum And Lateralitymentioning
confidence: 95%